Lead, cadmium, and selenium levels in maternal and umbilical cord blood and their relationships - Vida Nezhad Chehrazi; Lida Moghadam Banaem (Payesh, 2012)
Objective (s): To determine maternal and umbilical cord levels of lead, cadmium, and selenium and study their relationships.Methods: This was a cross-sectional study.  Sampling of mother's blood during delivery and cord blood after delivery were performed and the blood levels of the 3 mentioned elements were measured. P-values less than 0.05 were considered significant.Results: The significant correlations found were: positive correlations between maternal and cord lead(r=0.522), maternal  and cord cadmium (r= 0.733), maternal and cord selenium(r= 0.582), cord cadmium and maternal selenium(r=0.242), cord cadmium and cord selenium(r= 0.211), and negative correlations between maternal lead and selenium(r=-0.235), maternal lead and cord selenium(r=-0.271), maternal lead and cadmium(r=-0.377), cord cadmium and maternal lead(r= -0.387).Conclusion: In this study, cord blood lead and cadmium levels had direct correlations with maternal levels of them, and cadmium concentrations in cord blood were less than those in maternal blood, suggesting the more effective placental barrier for cadmium transferring from mother to fetus.  Selenium levels in cord blood had a direct correlation with maternal selenium levels, and were higher in cord blood, suggesting the active transfer of selenium to fetus.More studies in different populations of mothers and neonates are recommended to study these relationships more precisely.